파킨슨병 환자에서 위장관 운동조절제의 사용현황 및 처방에 미치는 요인 - 이창훈(Chang Hoon Lee), 김시인(Siin Kim), 서혜선(Hae Sun Suh) (Yaghag-hoi-ji, 2019)
Gastrointestinal motility drugs have been prescribed to manage functional dyspepsia in Parkinson’s disease(PD). However, anti-dopaminergic gastrointestinal motility drugs can exacerbate motor symptoms of PD. This studyinvestigated the current use and factors affecting prescription of gastrointestinal motility drugs in PD patients. Thisretrospective cohort study extracted 3 patient groups (high-risk anti-dopaminergic drugs, low-risk anti-dopaminergic drugsand trimebutine group), by using the National Health Insurance Service-National Sample Cohort database. The mostfrequently prescribed drug was domperidone (n=437). Age and Charlson comorbidity index (CCI) were significantlydifferent across three patient groups (p-value<0.05). Post hoc test (Tukey test) showed that high-risk group and trimebutinegroup were significantly different in age and CCI (p-value<0.05). The chi-square test for types of institution and clinicaldepartments were significantly different across patient groups (p-value<0.001). Compared to tertiary hospital, generalhospital [odds ratio (OR): 2.05, confidence interval (CI): 1.07-3.93], hospital/psychiatric hospital (OR: 4.28 CI: 2.11-8.65),and clinic (OR: 4.94 CI: 2.64-9.26) were more likely to prescribe high-risk drugs than low-risk drugs. Among clinicaldepartments, neurology (OR: 0.08 CI: 0.05-0.14) was less likely to prescribe high-risk drugs than low-risk drugs. Whencomparing low-risk drugs group and trimebutine group, low-risk drugs were less likely to be prescribed in general hospital(OR: 0.40 CI: 0.18-0.92), hospital/psychiatric hospital (OR: 0.24 CI: 0.10-0.58), and clinic (OR: 0.16 CI: 0.08-0.36) thanin tertiary hospital; Neurology (OR: 20.38 CI: 9.65-43.06) was more likely to prescribe low-risk drugs. Consequently,tertiary hospital and neurology were more likely to prescribe low-risk drugs than clinics and internal medicine, respectively. KCI Citation Count: 0